Implementasi Kebijakan Pencegahan dan Penanggulangan Stunting pada Anak di Nagari Sikilang Sungai Aur Selatan - Sinta, Friti; Hambali; Rizki, Muhammad; Alfiani, Nur Indah; Ramadhani, Varla; Husna, Zatil (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
This article aims to analyze the implementation of village-based prevention and control policies in Nagari Sikilang Sungai Aur Selatan, West Pasaman Regency. The problem is focused on optimizing the implementation of prevention policies through integrated health service posts (posyandu) activities, toddler home visits, and counseling for village cadres. In order to approach this problem, theoretical references from public policy and public health are used. Data were collected through in-depth interviews, counseling, and documentation, and analyzed qualitatively with a descriptive approach. This study concludes that the implementation of policies in Nagari Sikilang has not been optimal due to lack of facilities, minimal program supervision, and low public knowledge about prevention. In conclusion, it is necessary to improve facilities and public education so that policies are more effective